Physical, mental health versus socio-economic status of elderly citizens of suburbs of Kamrup (metro) district of Assam, India - Sarma, Jonali; Bardoloi, Jitendra Nath (International Journal Of Community Medicine And Public Health, 2024)
Background: Population ageing has insightful social, economic, and political consequences. Ageing in general is often associated with poor health, lack of independence, social declination, isolation, and loneliness. The elderly people face many problems due to factors such as limited or no income, intergenerational conflict, and even face abuse by family members. This study delves into to assess the socio-economic status, the physical and mental health conditions and to determine the association of socio-economic status with physical and mental health problems, among elderly citizens in the semi- urban areas of Kamrup (Metro), Assam, India. Methods: Total 250 elderly were included in the study. The primary data have been collected through personal interview from the respondents who had visited the health camps. Statistical analysis was done using SPSS 25. Results: Out of 250 elderly, 69.6% were female, majority (91.2%) were found to be Hindus, 68.67% were married. 46.53% of the respondents had attended primary school and 66.53% were unemployed. 87% elderly suffered from chronic illness. Cognitive Impairment was absent in majority of the elderly people (91%) whereas depressive symptoms were present in 11% respondents. 19.3% respondents had moderate nutritional risk. The association between nutritional risks and age was statistically significant. The association between nutritional risks and caste and educational level were also found to be statistically significant. Conclusion: The status of physical and mental health of this group of people has a significant relationship with the socio-economic status.